2007
DOI: 10.1111/j.1365-3059.2007.01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of secondary infection by Pythium violae in epidemics of carrot cavity spot using root transplantation as a method of soil infestation

Abstract: Cavity spot of carrot (CCS), one of the most important soilborne diseases of this crop worldwide, is characterized by small sunken elliptical lesions on the taproot caused by a complex of pathogens belonging to the genus Pythium , notably P. violae . In most soilborne diseases the soil is the source of inoculum for primary infections, with diseased plants then providing inoculum for secondary infections (both auto-and alloinfection). Using fragments of CCS lesions to infest soil, it was demonstrated that CCS l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The present experiment confirmed that a carrot taproot quickly produces new lateral roots and leaves regrow 2 weeks after transplantation (Suffert and Montfort 2007). Concomitantly with CCS lesions on taproots, brown to rustcolored microlesions were sometimes observed on carrot lateral roots, but Pythium species were rarely isolated from them (Suffert and Guibert 2007).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The present experiment confirmed that a carrot taproot quickly produces new lateral roots and leaves regrow 2 weeks after transplantation (Suffert and Montfort 2007). Concomitantly with CCS lesions on taproots, brown to rustcolored microlesions were sometimes observed on carrot lateral roots, but Pythium species were rarely isolated from them (Suffert and Guibert 2007).…”
Section: Discussionsupporting
confidence: 86%
“…The production of secondary inoculum of Pythium sp. has already been established (Burdon and Chilvers 1975;Green and Jensen 2000;Suffert and Montfort 2007); however, no study has firmly differentiated between spread by mycelia from that by zoospores. Microscopic examinations of P. ultimum in the bulk potting mix confirmed that the spread was due to active mycelial growth because no zoospores were observed in the soil (Green and Jensen 2000).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations